Methods of programming increased milk production and its relationship with sustainability of the dairy industry - Carpenter, Abigail Joy (Kansas State University, 2016)
High levels of milk production has been and will continue to be a priority for the global dairy industry. Non-steroidal antiinflammatory drugs administered to dairy cattle following calving can be an effective way of programming higher milk production for the entirety of lactation. When dairy cattle on a commercial dairy received either sodium salicylate or meloxicam following calving, they responded with increased whole-lactation milk production, which was driven by higher daily milk yields following the seventh week of lactation. When dairy cattle at a research dairy received sodium salicylate following calving, they did not show the same increase in milk production but feed intake, feeding behavior, and blood parameters were altered for an extended period of time. The response to treatment was largely dependent on the parity of the animal. In an effort to determine whether re-programming of the rumen environment could explain these findings, sodium salicylate was administered to batch cultures of rumen fluid, and as a result, fermentation was inhibited. When substrate was fermented in rumen fluid from heifers who had been dosed with sodium salicylate, fermentation was inhibited for an extended period of time following sodium salicylate administration. Beyond the use of compounds such as these, other factors can program lactation for higher milk production, including the gender of the calf. Analysis of lactation records from the US has indicated that cows produce more milk following the birth of a heifer calf compared to a bull. With further research, findings such as these can provide farmers with more tools for improving productivity and lead to the sustainability of the dairy industry as a whole.
Keywords: Animal sciences; Sustainability; Dairy cattle; Non-steroidal antiinflammatory drugs; Calf gender; Milk production